KRITERIA PENILAIAN PADA SIMULASI UJIAN STANDAR KEMAMPUAN BERBAHASA JERMAN BERBASIS CEFR MODUL BERBICARA INTERAKTIF (SPRECHEN) - Dasim Karsam (Jurnal SORA, 2022)
An examination is the only way to best measure, recognize and document the performance of learning. In the opinion of Funk et. al. (2020: 3), a new textbook implements the requirements of the expanded Common European Framework of Reference (CEFR) for Languages. This shows that knowledge of the assessment criteria, as well as skills in applying them, are very important for examiners to be able to make an accurate assessment of the following elements: (1) content; (2) expression, fluency; (3) vocabulary, socio-cultural aspects; (4) aspects of syntax, grammar; and (5) phonetic aspects. It is therefore very important for one to have knowledge of the rules and regulations regarding the assessment criteria required to administer the CERF-based speaking proficiency exam.